Reference values for the appendicular lean muscle index in healthy young Saudi women: a nutritional perspective - Alhussain, Maha H.; Alamro, Samar A.; Alghannam, Abdullah F.; Alabdullatif, Rawan A.; Alkahtani, Shaea (Frontiers in Nutrition, 2025)
BackgroundSarcopenia refers to the age-related decline in muscle function, including muscle strength and muscle mass. It can be diagnosed using the appendicular lean muscle index (ALMI) for specific populations. However, reference values for the ALMI in Saudi women are lacking.AimThis study aimed to determine the ALMI reference values in young Saudi women using bioelectrical impedance analysis (BIA). The relationship between ALM and dietary intake was also investigated.MethodsA total of 387 healthy young Saudi women, aged between 18 and 25 years, were included in this study. They were recruited through a convenience sampling method between October 2020 and June 2021. Body composition was assessed using BIA (Inbody 770). The ALMI was determined by calculating the sum of lean tissue in the arms and legs and dividing it by the height squared (ALM/h2). The cutoff value was calculated by deriving the −2 standard deviation (SD) value based on the participants’ data. A 24-h dietary recall was also conducted, and energy and macronutrient intakes were assessed.ResultsThe mean ALM/h2 was 5.63 ± 0.77 kg/m2, and the mean ALM/ht2, −2 SD value was 4.09 kg/m2 for the young Saudi reference group. There were significant positive correlations between ALM and protein (g/day) (r = 0.15; p < 0.001), protein (%) (r = 0.16; p = 0.002), fiber (g/day) (r = 0.21; p < 0.001), and cholesterol (mg/day) (r = 0.14; p = 0.007). However, the ALM showed a significant negative correlation with carbohydrates (%) (r = − 0.11; p = 0.03).ConclusionThese findings provide valuable reference values for evaluating ALM in patients with a variety of diseases that impact ALM. Furthermore, a cutoff value for low ALM may assist in the diagnosis of sarcopenia in Saudi women and enhance our understanding of the effects of total dietary nutrient intake on sarcopenia.